Effect of maitake mushrooms thick extract on the state of antioxidant system in rats with DMH-induced colon carcinogenesis - І. І. Herasymets; L. S. Fira; І. І. Medvid (The State Expert Center of the Ministry of Health of Ukraine, 2023)
Colorectal cancer is a dangerous oncological disease that requires serious complex treatment. This type of oncopathology occurs due to atypical growth of the epithelium of the mucous layer that lines the intestinal walls. Colon cancer is characterized by slow development, so prevention and timely diagnosis are a priority. The main advantage of using oncoprotectors based on natural raw materials in clinical practice is their low toxicity and the possibility of long-term use without significant side effects. That is why the development and study of such drugs are relevant. The aim of the research was to study indicators of oxidative processes and antioxidant systems in rats with chemically induced colon carcinogenesis against the background of maitake mushrooms thick extract use. The study was performed on 120 white male rats weighing 190-210 g. Adenocarcinoma of the colon was modeled by administering 1,2-dimethylhydrazine (DMH) hydrochloride for 30 weeks (1 time per week). A thick extract from maitake mushrooms was administered intragastrically daily at a dose of 150 mg/kg of animal body weight. Blood and liver samples were taken for research monthly. The state of the pro- and antioxidant systems was studied by the content of oxidative modification of proteins products neutral and alkaline character, superoxide dismutase and catalase activity, contents of reduced glutathione and ceruloplasmin. It was found that DMH-induced colon carcinogenesis in rats is accompanied by an increase in the activity of free radical oxidation processes. It is evidenced by a decrease in superoxide dismutase activity, catalase activity, a significant reduction in the content of reduced glutathione, an increase in the content of ceruloplasmin and products of oxidative modification of proteins in the blood serum and liver of animals. The effectiveness of maitake mushrooms thick extract and its positive influence on the activity of the studied enzymes and the content of OMP products in investigated tissues was experimentally proved. The use of maitake mushrooms thick extract under conditions of DMH-induced colon carcinogenesis in rats led to the normalization of antioxidant protection indicators and a significant decrease in the indicators of oxidative modification of proteins, which testifies to the suppression of oxidative stress in animals with an oncological process.